High resolution 16S rRNA gene Next Generation Sequencing study of brain areas associated with Alzheimer’s and Parkinson’s disease - Emery, David C.; Davies, Maria; Cerajewska, Tanya L.; Taylor, Jelena; Hazell, Mae; Paterson, Alex; Allen-Birt, Shelley J.; West, Nicola X. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s (AD) and Parkinson’s disease (PD) are neurodegenerative conditions characterised by incremental deposition of proteinaceous pathologies in relatively conserved patterns. Both are associated with neuroinflammation, and a proposed microbial component for disease initiation and/or progression. Notably, -amyloid in AD, and α-synuclein in PD, have been shown to possess antimicrobial properties. Previous studies have provided evidence for bacterial presence within the brain, including the oral subgingival pathobiont Porphyromonas gingivalis (P.gingivalis). Cognitive impairment and brain pathology have been linked in several different studies to periodontal (gum) disease, particularly in AD, whilst gum disease, and also gut dysbiosis, have been linked to PD. Here, we use high resolution 16S rRNA gene Next Generation Sequencing (16S NGS) to characterise bacterial composition in brain areas associated with early, intermediate and late-stage disease. This has revealed the widespread presence of bacteria, predominantly oral, some subgingival and oronasal, in areas of the brain associated with AD and PD pathology. Furthermore, brain areas which may be associated with early disease development were substantially different in bacterial DNA content compared to areas affected later in disease aetiology